2020
DOI: 10.21037/jtd-20-2382
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam CT imaging for bronchoscopy: a technical review

Abstract: Cone beam computed tomography (CBCT) is a well-established imaging modality with numerous proven applications across multiple clinical disciplines. More recently, CBCT has emerged as an important imaging tool for bronchoscopists, primarily used during transbronchial biopsy of peripheral pulmonary lesions (PPLS). For this application CBCT has proved useful in navigating devices to a target lesion, in confirming device tool-in-lesion, as well as during tissue acquisition. In addition, CBCT is poised to play an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 38 publications
1
42
0
1
Order By: Relevance
“…Verhoeven et al indicated CBCT to be a valuable addition to ENB, reporting a 35.3% increase in navigation success (12). A recent study summarized the value of CBCT imaging applied for bronchoscopy, such as instrument navigation, "tool-in-lesion" confirmation, and ablation evaluation in all phases of bronchoscopy (13). These studies suggest that CBCT has the potential to become a standard technique in this growing field.…”
Section: Discussionmentioning
confidence: 99%
“…Verhoeven et al indicated CBCT to be a valuable addition to ENB, reporting a 35.3% increase in navigation success (12). A recent study summarized the value of CBCT imaging applied for bronchoscopy, such as instrument navigation, "tool-in-lesion" confirmation, and ablation evaluation in all phases of bronchoscopy (13). These studies suggest that CBCT has the potential to become a standard technique in this growing field.…”
Section: Discussionmentioning
confidence: 99%
“…Some mobile C-arm systems-including Cios Spin (Siemens Healthineers) and Vision RFD 3D (Ziehm Imaging, Florida, USA)-are also able to perform CBCT. Although mobile C-arms have a smaller field of view and a longer image acquisition time of ~30-60 s, they can move easily, and have a smaller footprint and more acceptable price [112].…”
Section: Cone-beam Computed Tomography (Cbct)mentioning
confidence: 99%
“…Fluoroscopy and cone-beam computed tomography (CBCT) may help overcome these limitations (15,16). CBCT provides intraprocedural three-dimensional imaging from which structures of interest can be extracted and overlaid on fluoroscopy: this augmented fluoroscopy provides a real-time three-dimensional roadmap guidance that has been shown to increase endobronchial biopsies' diagnostic yield when used with ENB (17,18).…”
Section: Introductionmentioning
confidence: 99%